Work-related stress in forensic mental health professionals: a systematic review. Issue 3 (14th August 2017) - Brown, Darcy; Igoumenou, Artemis; Mortlock, Anna-marie; Gupta, Nitin; Das, Mrigendra
Abstract : Purpose: The purpose of this paper is to investigate the prevalence of stress and burnout among forensic mental health (FMH) professionals. Design/methodology/approach: A systematic review of the available literature accessed by relevant databases was conducted. Findings: This study concluded that FMH suffer from moderate levels of both stress and burnout. There is insufficient evidence to establish that they suffer from higher levels of stress than their non-forensic colleagues. Interventions such as psychosocial intervention training have been reported to demonstrate an improvement in staff knowledge and attitudes towards patients, whilst reducing burnout. Practical implications: Stress in FMH is a cause of concern. Conclusions drawn are applicable only to nursing staff as other professions were not adequately represented. As most studies used the burnout scores, results were directly comparable. Further research is needed to fully evaluate stress and burnout in professionals who work within FMH settings. Originality/value: High levels of stress and burnout have negative effects on an individual's ability to work and subsequently there is a financial and also moral incentive for the management of health service workforces to intervene. This study highlights that FMH, as a population, are at risk.